Cannibalism by the juveniles of the gastropod Rapana venosa (Muricidae) reared under laboratory conditions. (21st June 2018) - Yu, Zheng-Lin; Wang, Hao; Song, Hao; Bai, Yu-Cen; Sun, Jing-Chun; Qian, Yao-Sen; Hu, Nan; Yang, Mei-Jie; Zhang, Tao
Abstract: We report extreme cannibalistic behaviour in juveniles (1.5–10 mm) of the rapa whelk, Rapana venosa, when they transition from a phytophagous to a carnivorous feeding habit after metamorphosis, as appropriate food becomes scarce during this stage. Although cannibalism is beneficial for the individual, it can result in a high mortality rate of juvenile R. venosa as a whole, therefore juvenile cannibalism is an important determinant of population size. We observed both hole-drilling and enveloping methods of cannibalism. The inner borehole diameter on prey was positively correlated with shell height of the predator ( P < 0.001). A higher cannibalism rate was mainly caused by small body size, high levels of hunger and high juvenile densities. The cannibalism rate was effectively controlled by offering bivalves, such as Ruditapes philippinarum and Argopecten irradians, as food. Our results broaden the understanding of cannibalistic behaviour in gastropods and can be used to develop or improve commercial breeding strategies for R. venosa .